Age Limit for Marriage in Indonesia from The Perspective of Maqashid Sharia - Faizal, Liky; Qohar, Abd.; Wakhid, Ali Abdul; Susanto, Is (Analisis: Jurnal Studi Keislaman, 2022)
The age of marriage regulated in the Law states that the age allowed for marriage is 19 years for both men and women. In the current context, this age is considered quite ideal. However it will raise problems if the marriage is done too young, especially health problems. Other factors can be in the form of psychological problems, education, economy and others. This study uses a qualitative method of library research with a Systematic Literature Review (SLR) approach. This approach is used for various research procedures that are systematic by examining and reviewing the literature. The theory used as an analytical knife is the maqashid syari'ah theory, and at the end of the analysis this study uses deductive logic thinking. The results of the study show that the age limit for marriage in Indonesia is regulated in Law no. 6 of 2019 in article 7 paragraph (1). When viewed from the perspective of maqasid al-shari'ah, the most important thing in terms of the age limit of marriage is benefit associated with al-kulliyyatu al-khamsah, when viewed from the five main elements of maqasid al-shari'ah, then hifdh nasl is not only about caring for offspring, not  merely obtaining offspring from a legal marriage relationship, but maintaining these offspring as healthy and quality offspring.